The Relationship Between Profitability, Managerial and Institutional Ownership on Carbon Emission Disclosure - Agung Rizki Dwi Putra; Enggar Diah Puspa Arum; Rico Wijaya Z (Greenation International Journal of Economics and Accounting, 2025)
This study examines the relationship between profitability, managerial ownership, and institutional ownership with carbon emission disclosure in energy sector companies listed on the Indonesia Stock Exchange during the period 2021 to 2023. Carbon emission disclosure is a form of corporate environmental accountability that reflects transparency and commitment to sustainability. Using stakeholder theory as the theoretical framework, this study employs purposive sampling and obtains a sample of 20 companies with 60 firm-year observations. The data is collected from secondary sources, such as annual and sustainability reports, and analyzed using panel data regression with the EViews 12 software. The results show that profitability and managerial ownership are positively associated with carbon emission disclosure, while institutional ownership shows no significant relationship. These findings suggest that internal financial performance and ownership by management contribute to increased environmental transparency, whereas institutional investors may not consistently influence disclosure practices in the energy sector.